2011
DOI: 10.1021/ol2010159
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated “B-Entacenes”: Polycyclic Aromatics Containing Two Borepin Rings

Abstract: The synthesis and characterization of functionalized bora-acenes (B-entacenes) where Stille and Sonogashira cross-couplings were used to attach a series of electron-donating and -withdrawing substituents is reported. Photophysical, electrochemical, and computational analyses revealed that the LUMO level can be tuned by changing the para-conjugated substituent. Furthermore, the dimethylamino-functionalized molecule exhibited intense solvatochromism due to the intramolecular charge-transfer interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…The first compound containing two borepin rings was synthesized by Caruso et al . in 2010 and was nicknamed “ para‐B ‐entacene” ( 49 CCDC#762997) because the borons are para relative to the central benzene ring and the compound was a heteronuclear analogue of pentacene . The meta‐B ‐entacene ( 50 CCDC#875568) was synthesized soon thereafter by Levine et al .…”
Section: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first compound containing two borepin rings was synthesized by Caruso et al . in 2010 and was nicknamed “ para‐B ‐entacene” ( 49 CCDC#762997) because the borons are para relative to the central benzene ring and the compound was a heteronuclear analogue of pentacene . The meta‐B ‐entacene ( 50 CCDC#875568) was synthesized soon thereafter by Levine et al .…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Unfortunately, assigning the chemical shifts of the olefinic borepin protons proved too difficult, and therefore the induced ring current could not be compared to other molecules using 1 H NMR spectroscopy. Despite the lack of strong aromaticity in the borepin rings (or perhaps because of), the compounds were stable to a variety of palladium catalyzed cross‐coupling reactions that made extensions onto the core as well as polymerizations possible . The ability to synthesize new borepin compounds with functional handles demonstrated their possible applications as π‐conjugated electronic materials …”
Section: Recent Developmentsmentioning
confidence: 99%
“…As we were completing our initial studies, Warren Piers reported the synthesis of benzo‐ and naphtho‐fused borepins in the context of blue light‐emitting materials (Figure b) . The forward synthesis we developed for the parent dibenzoborepins essentially mirrored the Piers synthesis, and we further showed how this route could be applied to functionalizable cores (by virtue of installed aryl chlorides) as well as even more complex molecular structures containing two fused borepin rings (Figure c) …”
Section: Hückel's N = 1: Boron‐containing Heteroaromaticsmentioning
confidence: 89%
“…[1][2][3][4][5][6] Heteropines incorporated heteroatoms such as B,7,8 Al, 9 Ga, 10,11 Si, 12,13 Ge, 14 Sn, 15 P, 16,17 As, 18 Bi, 18 and Se. 14 B-heteropine, denoted as borepin with a heterocyclic ring containing only boron and carbon atoms was used by Letsinger et al 19 in 1955.…”
Section: Introductionmentioning
confidence: 99%
“…15 Tovar and co-workers reported para-and meta-B-entacene, respectively, containing two borepin rings with stable structure in air for months purified by silica gel chromatography. 5,7,8 In this contribution, we reported the design, organocatalysis synthesis, and characterization of the original example of seven member stable 3H-pyrrolizine fused diazaborepin via B-N chemistry. 22 Different from previous routes, 23 3H-pyrrolizine fused 'naked' diazaborepin under one step organocatalyzed condensation reaction was obtained directly.…”
Section: Introductionmentioning
confidence: 99%